Metabolic Reprogramming Mediates Delayed Apoptosis of Human Neutrophils Infected With Francisella tularensis - Krysa, Samantha J.; Allen, Lee-Ann H. (Frontiers in Immunology, 2022)
Neutrophils (polymorphonuclear leukocytes, PMNs) have a distinctively short lifespan, and tight regulation of cell survival and death is imperative for their normal function. We demonstrated previously that Francisella tularensis extends human neutrophil lifespan, which elicits an impaired immune response characterized by neutrophil dysfunction. Herein, we extended these studies, including our transcriptional profiling data, and employed Seahorse extracellular flux analysis, gas chromatography-mass spectrometry metabolite analysis, flow cytometry and several other biochemical approaches to demonstrate that the delayed apoptosis observed in F. tularensis-infected neutrophils is mediated, in part, by metabolic reprogramming. Specifically, we show that F. tularensis-infected neutrophils exhibited a unique metabolic signature characterized by increased glycolysis, glycolytic flux and glucose uptake, downregulation of the pentose phosphate pathway, and complex glycogen dynamics. Glucose uptake and glycolysis were essential for cell longevity, although glucose-6-phosphate translocation into the endoplasmic reticulum was not, and we identify depletion of glycogen as a potential trigger of apoptosis onset. In keeping with this, we also demonstrate that ablation of apoptosis with the pan-caspase inhibitor Q-VD-OPh was sufficient to profoundly increase glycolysis and glycogen stores in the absence of infection. Taken together, our data significantly advance understanding of neutrophil immunometabolism and its capacity to regulate cell lifespan.